Matrix stiffness controls lymphatic vessel formation through regulation of a GATA2-dependent transcriptional program - Frye, Maike; Taddei, Andrea; Dierkes, Cathrin; Martinez-Corral, Ines; Fielden, Matthew; Ortsäter, Henrik; Kazenwadel, Jan; Calado, Dinis P.; Ostergaard, Pia; Salminen, Marjo; He, Liqun; Harvey, Natasha L.; et al. (Nature communications, 2018)
Tissue and vessel wall stiffening alters endothelial cell properties and contributes to vascular dysfunction. However, whether extracellular matrix (ECM) stiffness impacts vascular development is not known. Here we show that matrix stiffness controls lymphatic vascular morphogenesis. Atomic force microscopy measurements in mouse embryos reveal that venous lymphatic endothelial cell (LEC) progenitors experience a decrease in substrate stiffness upon migration out of the cardinal vein, which induces a GATA2-dependent transcriptional program required to form the first lymphatic vessels. Transcriptome analysis shows that LECs grown on a soft matrix exhibit increased GATA2 expression and a GATA2-dependent upregulation of genes involved in cell migration and lymphangiogenesis, including VEGFR3. Analyses of mouse models demonstrate a cell-autonomous function of GATA2 in regulating LEC responsiveness to VEGF-C and in controlling LEC migration and sprouting in vivo. Our study thus uncovers a mechanism by which ECM stiffness dictates the migratory behavior of LECs during early lymphatic development. Mechanical cues are known to influence endothelial cell behavior. Here Frye et al. show that lymphatic endothelial cell progenitors experience varying degrees of matrix stiffness during development, and that matrix stiffness regulates GATA2 expression to drive lymphatic vessel formation.